2004
DOI: 10.1016/j.combustflame.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Formation of HNCO, HCN, and NH3 from the pyrolysis of bark and nitrogen-containing model compounds

Abstract: Bark pellets have been pyrolyzed in a fluidized bed reactor at temperatures between 700 and 1000 • C. Identified nitrogen-containing species were hydrogen cyanide (HCN), ammonia (NH 3 ), and isocyanic acid (HNCO). Quantification of HCN and to some extent of NH 3 was unreliable at 700 and 800 • C due to low concentrations. HNCO could not be quantified with any accuracy at any temperature for bark, due to the low concentrations found. Since most of the nitrogen in biomass is bound in proteins, various protein-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
213
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(236 citation statements)
references
References 48 publications
(71 reference statements)
11
213
1
3
Order By: Relevance
“…8c where HNCO is correlated with CO measurements (interpolated to a 1-s timeline). The HNCO/CO flaming stage slope is 0.28% in this experiment, and is likely related to the C/N pyrolysis chemistry that takes place in biomass burning (Hansson et al, 2004). The only compound that can be compared between the inorganic acids measured by the NI-PT-CIMS and the instack FTIR instrument is HONO.…”
Section: Application Of Ni-pt-cims To Biomass Burning Measurementsmentioning
confidence: 81%
See 2 more Smart Citations
“…8c where HNCO is correlated with CO measurements (interpolated to a 1-s timeline). The HNCO/CO flaming stage slope is 0.28% in this experiment, and is likely related to the C/N pyrolysis chemistry that takes place in biomass burning (Hansson et al, 2004). The only compound that can be compared between the inorganic acids measured by the NI-PT-CIMS and the instack FTIR instrument is HONO.…”
Section: Application Of Ni-pt-cims To Biomass Burning Measurementsmentioning
confidence: 81%
“…While cyanate salts, such as sodium cyanate (NaOCN), are known to be stable, they evolve HNCO vapor upon acidification (Fischer et al, 2002), and HNCO has been shown to be the most thermodynamically stable of the possible CHNO isomers (Mladenovic and Lewerenz, 2008). There are several studies of the pyrolysis of biomass, coal, and polyamides, that have unambiguously identified HNCO as a major product by infrared spectroscopy (Hansson et al, 2004;Nelson et al, 1996). As a result of these studies and the above chemical considerations, the signal at mass 42 is assigned to HNCO.…”
Section: Isocyanic Acid (Hnco)mentioning
confidence: 99%
See 1 more Smart Citation
“…Quaternary forms of nitrogen are also present, especially in low-rank coals. Amine functionalities are observed in low-rank coals [160], while they are present in biomass in diverse forms: proteins [161,162] (polymer of amino acids), alkaloids (heterocyclic nitrogen compounds), non-protein amino acids, nucleic acids, inorganic nitrogen and chlorophyll [163]. Chlorophyll, the green coloring matter in leaves and green stems, contains N in a magnesium-containing pyrrole derivative.…”
Section: Effect Of Blending Coal and Biomass/waste On No X And N 2 O mentioning
confidence: 99%
“…Ren and Zhao [175] studied the pyrolysis and O 2 and CO 2 gasification behavior of phenylalanine, aspartic acid and glutamic acid in a TGA at temperatures ranging from 0 K to1073 K. The distinct structures of these amino acids cause them to behave slightly differently under argon pyrolysis as well as O 2 and CO 2 gasification. Ren et al [176] found that the structure of the amino acids, the mineral matter content of biomass [178,179], the pyrolysis/gasification condition and the particle size [161,180] affects significantly the fate of nitrogen during pyrolysis of biomass. The thermal decomposition of amino acids and proteins proceeds mainly through dehydration with formation of cyclic amides, with diketopiperazine (DKP) being the common one [172][173][174]177].…”
Section: Fuel Nitrogen Behavior During Biomass Conversionmentioning
confidence: 99%